From byssus threads to Pinna nobilis sea-silk: a fiber characterization - Lorena C. Giannossa; Annarosa Mangone; Giovanni Lagioia; Gerardo Palazzo; Luigi Gentile (Academia Materials Science)
Sea-silk is made from the byssus threads of Pinna nobilis, an endemic species found in the Mediterranean. The fibers are carefully harvested by cutting them off the mussel, after which they undergo a series of processes including washing, drying, combing, and spinning. The end result is an exceptionally fine, distinctive, and highly valuable fabric. Pinna nobilis byssus is non-collagenous-based, and the fiber's nanostructure is still poorly understood. In this study, we present an investigation into Pinna nobilis byssus samples collected from the Commodity Science Museum of the University of Bari Aldo Moro (Italy) at various stages of the textile manufacturing process. Through scanning electron microscopy (SEM), we reveal a distinctive elliptical cross-section of the Pinna nobilis byssus fibers. Additionally, by using wide-angle X-ray diffraction (WAXRD) and infrared (IR) spectroscopy, we discover hydroxyapatite adsorbed onto the initial fibers. This finding provides intriguing insights into the composition and potential functional properties of the byssus threads. Furthermore, using a WAXRD-based method, we observe a decrease in the crystalline/amorphous ratio during the byssus treatment process. This finding suggests the occurrence of structural modifications as the fibers undergo manufacturing steps, potentially influencing the properties of the final sea-silk fabric.